2016
DOI: 10.1007/s11192-016-2013-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and efficiency of research in Germany over time: an analysis of German business schools between 2001 and 2009

Abstract: This article analyses the development of effectiveness and efficiency of German business schools' research production between 2001 and 2009. The results suggest that effectiveness for most of the examined business schools increases initially. Then, however, a declining trend in the further course of time can be observed. Similar tendencies can be stated considering efficiency, even though they are slightly less pronounced. An analysis of the reasons for these observations reveals that the initial positive deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 45 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…These models assume that all inputs are devoted to the first process to produce certain intermediate products, which are, in turn, the inputs of the second process to produce the final outputs. Besides opening the black box, other scholars have resorted to evaluate the adjustment between the production of HEIs and the results expected from them (i.e., effectiveness), such as those of Clermont (2016), Powell et al (2012), and Thanassoulis et al (2018). Other network structures, although less common, are the parallel structure (7 articles) and the general structure in two stages (2 articles).…”
Section: Structure Of the Modelsmentioning
confidence: 99%
“…These models assume that all inputs are devoted to the first process to produce certain intermediate products, which are, in turn, the inputs of the second process to produce the final outputs. Besides opening the black box, other scholars have resorted to evaluate the adjustment between the production of HEIs and the results expected from them (i.e., effectiveness), such as those of Clermont (2016), Powell et al (2012), and Thanassoulis et al (2018). Other network structures, although less common, are the parallel structure (7 articles) and the general structure in two stages (2 articles).…”
Section: Structure Of the Modelsmentioning
confidence: 99%
“…Thus, evaluation and management of R&D performance are now an important consideration in national R&D activities (So 2011). Clermont (2016) revealed that the initial positive developments of effectiveness and efficiency are mainly due to technology advances, whereas the following decreases are basically a result of technology backwardness. Wei et al (2016) pointed out that a country has also increased the input of technology and R&D to prompt technological reformation and imported technology absorption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent decades, researchers have devoted increasing attention to new trends and topics in the business domain (Clermont, 2016;Wei and Zhang, 2020b). For example, based on an analysis of business schools from 2001 to 2009, Clermont (2016) described the development of the effectiveness and efficiency of research in German business schools and analyses the reasons for these changes.…”
Section: Introductionmentioning
confidence: 99%